How Query Violations Relate to Relevance in Product Search - S. F. Paula, Felipe; Kuhn, Daniel Matheus; P. Moreira, Viviane (Anais do Simpósio Brasileiro de Banco de Dados (SBBD); 2026: Anais do XLI Simpósio Brasileiro de Bancos de Dados, 2026)
The concept of relevance has underpinned the research in Information Retrieval since its early days. Specifically, in eCommerce search, where queries typically involve attributes that express constraints, relevance is affected by how well those constraints are satisfied. However, the relationship between relevance and constraint violations was overlooked in existing research. In this work, we analyze 5,000 queries and 50,000 query-product pairs to investigate whether query-intent violation constitutes a ranking signal related to, but distinct from, graded relevance. Our results show that violation is related to, but not reducible to, graded relevance. We further show that simple violation-aware features substantially reduce query violations and remain competitive with, or even slightly improve upon, strong baselines on retrieval quality metrics.